Edukasi ISI PIRINGKU Menggunakan Booklet Pada Masyarakat di Wilayah Kerja Puskesmas Karanganyar Kabupaten Lampung Selatan - Fitri Windari; Kholis Khoirul Huda (Pelantar Press, 2024)
Malnutrition is still a serious health scourge in Indonesia, especially in rural areas. National Health Research (Riskesnas) 2021 shows that the prevalence of stunting in children under five in Indonesia still reaches 24.6%. This figure shows that there are still many children in Indonesia who lack adequate nutritional intake. One effort to overcome the problem of malnutrition is to educate the public about a balanced diet. ISI PIRINGKU is presented as a balanced nutritional guide that is easy to implement and in accordance with local culture. This guide divides the plate into half containing complex carbohydrates, such as brown rice, sweet potatoes, or corn; a quarter of the plate contains protein, such as fish, chicken, or tempeh; and a quarter of the plate contains vegetables and fruit